TEACHER EDUCATION AND GLOBAL STANDARD FOR EFFECTIVE TEACHINGLEARNING PROCESS IN PUBLIC SECONDARY SCHOOLS IN CALABAR MUNICIPALITY, CROSS RIVER STATE, NIGERIA - Bassey Enya David; Josephine Dasel Nanjwan (European Scientific Journal, ESJ, 2014)
The paper aimed at investigating whether the current global education standards introduced in the teacher education influence effective teaching-learning process in Public Secondary Schools in Calabar Municipality, Cross River State in Nigeria. Two hundred (200) respondents made up of certificate teachers drawn from selected public secondary schools in Calabar Municipality, Cross River State, Nigeria with aid of a stratified random sampling technique constituted the sample of the study. Pearson’s Product Moment Correlation and independent t-test statistics were employed at 0.05 level of significance to analyze the data generated from administration of a self-designed Teacher Education and Global Standards in Secondary Schools Questionnaire (TEGSSQ) analysis of Hypothesis one showed a significant relationship between six education global standards and teachers education. The analysis of hypothesis two clearly revealed that males and females do not differ significantly in their perception of global and national education standards as weapons for effective teaching-learning process in public secondary schools in the study area. The results were exhaustively discussed. Useful recommendations were proffered and conclusion drawn on the basis of the results.